Designing a Disaster Resilient Community in Flood prone zones of Srinagar, Uttarakhand. - Kartikay Puri; Ayush Aryan (International Journal of Environmental Planning and Development Architecture, 2024)
Uttarakhand, a state that scuffles with the dual challenges of climate change and rapid development, is particularly vulnerable to devastating floods. This research delves into the critical issue of strengthening community resilience against such disasters. By examining the interconnected factors of preparedness, mitigation, and response, the study aims to develop a robust framework for safeguarding lives and livelihoods in flood-prone regions. A cornerstone of this research is the exploration of traditional knowledge systems, which have proven invaluable in predicting and responding to natural hazards. Coupled with modern early warning systems and meticulously planned evacuation procedures, these insights can significantly enhance a community's ability to anticipate and prepare for floods. Moreover, the study underscores the importance of mitigation strategies, such as constructing flood-resistant infrastructure and implementing sustainable land management practices. These measures can effectively reduce the impact of floods and build long-term community resilience. The research also emphasizes the role of community-driven initiatives in ecosystem restoration. By revitalizing natural habitats, communities can enhance their environment's capacity to absorb excess water, thereby mitigating flood risks. This approach not only protects against disasters but also contributes to overall ecological health. By comprehensively analyzing these facets of flood resilience, the study offers a blueprint for creating safer and more sustainable communities in Uttarakhand. The findings are particularly relevant to Srinagar, a region identified as highly vulnerable to flooding. Ultimately, this research provides invaluable guidance for policymakers, community leaders, and disaster management agencies in their efforts to build resilient communities capable of weathering the challenges posed by climate change and extreme weather events. The research seeks to empower communities to take ownership of their safety and well-being, fostering a proactive approach to disaster management. By integrating traditional wisdom with modern scientific knowledge, this study offers a promising path toward a more resilient future for Uttarakhand and other flood-prone regions
Keywords: Vulnerable; disaster management; flood mitigation; mitigation; preparedness